Temperature-Insensitive Second-Order Microring Resonator for Dense Wavelength Division Multiplexing (DWDM) - Fuling Wang; Xiao Xu; Chonglei Sun; Liuge Du; Jia Zhao (IEEE Photonics Journal)
To achieve temperature-insensitive passband responses of microring resonator (MRR) for DWDM signal processing, we design and fabricate a wavelength division multiplexer with four channels based on 2nd-order slot MRR with PMMA cladding layer. Four filters with different radii are connected in series to realize 1.5-nm channel space. In the process of design and optimization, the dense wavelength demultiplexer (DEMUX) exhibits admirable responses with broad 1-dB bandwidth (>0.64 nm, accounting for 43% of the channel spacing), steep band edge (shape factors ∼0.47) and high temperature stability (temperature-dependent wavelength shift (TDWS) < 0.25 pm/°C, which is 0.4% of ordinary MRR). Then the device is fabricated and measured. The box-type responses are obtained for all 4 wavelength channels. The measured 1-dB bandwidth is 1.1 nm and the shape factor is larger than 0.35. Due to the fabrication imperfections and process errors, the central wavelengths shifted from ideal values. The measured TDWS is less than 24.8 pm/°C, which is deteriorated from the design due to the incomplete filling of the PMMA cladding in the slot. Even so, the decrease of the TDWS, combined with the box-type response of 1-dB bandwidth of 1.1 nm in our design, makes the DEMUX tolerate the temperature variation of larger than ±22 °C without the help of electrical temperature control. The results indicate the great potential of the designed device for DWDM applications.